2021
DOI: 10.7150/ijbs.56833
|View full text |Cite
|
Sign up to set email alerts
|

3,3'-Diindolylmethane induces gastric cancer cells death via STIM1 mediated store-operated calcium entry

Abstract: 3,3'-Diindolylmethane (DIM), a natural phytochemicals isolated from cruciferous vegetables, has been reported to inhibit human gastric cancer cells proliferation and induce cells apoptosis as well as autophagy, but its mechanisms are still unclear. Store-operated calcium entry (SOCE) is a main Ca 2+ influx pathway in various of cancers, which is activated by the depletion of endoplasmic reticulum (ER) Ca 2+ store. Stromal interaction molecular 1 (STIM1) is the nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Kaempferol, p-Coumaric acid, Astragalin and Tiliroside influence abnormal glycosylation of GC cells, so as to exert the anticancer effect ( Radziejewska et al, 2022 ). DIM suppressed GC via mediated ferroptosis, store-operated calcium entry, gastric cancer-derived mesenchymal stem cells, endogenous hydrogen sulfide biosynthesis ( Ye et al, 2020 ; Ye et al, 2021b ; Shi et al, 2021 ; Ye et al, 2022 ). It is reported that phytochemicals showed anticancer properties against GC associated with tumor viral infections ( Liskova et al, 2021 ; Sudomova et al, 2021 ).…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“…Kaempferol, p-Coumaric acid, Astragalin and Tiliroside influence abnormal glycosylation of GC cells, so as to exert the anticancer effect ( Radziejewska et al, 2022 ). DIM suppressed GC via mediated ferroptosis, store-operated calcium entry, gastric cancer-derived mesenchymal stem cells, endogenous hydrogen sulfide biosynthesis ( Ye et al, 2020 ; Ye et al, 2021b ; Shi et al, 2021 ; Ye et al, 2022 ). It is reported that phytochemicals showed anticancer properties against GC associated with tumor viral infections ( Liskova et al, 2021 ; Sudomova et al, 2021 ).…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“…One-way analysis of variance was used to calculate the significant differences among groups. A value of P < 0.05 was considered significant [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that DIM is known to induce apoptosis and autophagy via IP3R-mediated ER calcium store Ca 2+ release in gastric cancer [18]. However, the role of IP3R in DIM-induced ferroptosis has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,3-diindolylmethane (DIM) is a natural product found in cruciferous edible plants, such as cauliflower, cabbage, and broccoli. Previous studies have reported that DIM has several preventive effects, especially displaying anti-tumor, anti-inflammatory, antioxidant and free radical scavenging roles ( Luo et al, 2018 ; Ye et al, 2021 ). Recent studies have determined that DIM also protects against kidney, heart, and liver damage.…”
Section: Introductionmentioning
confidence: 99%